A Novel Mouse Model of Inflammatory Bowel Disease Links Mammalian Target of Rapamycin-Dependent Hyperproliferation of Colonic Epithelium to Inflammation-Associated Tumorigenesis - Deng, Lin (American Society for Investigative Pathology, 2010)
Inflammatory bowel disease (IBD) is a high-risk condition for human colorectal cancer. However, our mechanistic understanding of the link between inflammation and tumorigenesis in the colon is limited. Here we established a novel mouse model of colitis-associated cancer by genetically inactivating signal transducer and activator of transcription 3 (Stat3) in macrophages, with partial deletion in other myeloid and lymphoid cells. Inflammation developed in the colon of mutant mice spontaneously, and tumor lesions, including invasive carcinoma, arose in the inflamed region of the intestine with a frequency similar to that observed in human IBD patients. The development of both inflammation and tumors in the mutant mice required the presence of microflora. Indeed, inflammation was associated with disruption of colonic homeostasis, fulminant epithelial/tumor cell proliferation, and activation of the mammalian target of rapamycin (mTOR)-Stat3 pathway in epithelial and tumor cells. The activation of this pathway was essential for both the excess proliferation of epithelial/tumor cells and the disruption of colonic homeostasis in the mutant mice. Notably, a similar abnormal up-regulation of mTOR-Stat3 signaling was consistently observed in the colonic epithelial cells of human IBD patients with active disease. These studies demonstrate a novel mouse model of IBD-colorectal cancer progression in which disrupted immune regulation, mTOR-Stat3 signaling, and epithelial hyperproliferation are integrated and simultaneously linked to the development of malignancy.